Implementation Of The Policy For The Protection Of Women And Children Victims Of Violence In Buru Regency Maluku Province - Dian Ristanti; Deti Mulyati; Sampara Lukman (Jurnal Scientia, 2024)
In this research, the author took the title "Implementation of Policies for the Protection of Women and Children Victims of Violence in Buru Regency, Maluku Province". This research is intended to determine the implementation of the policy for the protection of women and children victims of violence, and the inhibiting factors in the implementation of the policy for the protection of women and children victims of violence in Buru Regency. The theory used in this research is the Implementation theory put forward by Van Meter and Van Horn. This research uses a descriptive qualitative method with an inductive approach. Research data was collected using interview, observation and documentation techniques. Based on the research conducted, the author concludes that the process of implementing regional regulations regarding the implementation of protection for women and children victims of violence in Buru Regency has not run optimally due to unsupportive geographical conditions, lack of facilities and infrastructure, lack of adequate human resources, minimal funding and lack of public knowledge regarding regional regulations implementing the protection of women and children victims of violence.